Research status of cluster nursing in pain management (集束化护理在疼痛管理中的应用现状) - WANG Yuqing (汪宇青); LI Chen (李晨) (中西医结合护理)
The pain management is a key indicator of measuring the quality of hospital medical service. This paper summarized the research status and development trend of cluster nursing in pain management such as surgical pain and cancer pain, and provided reference for the in-depth study of cluster nursing in pain management. (疼痛管理是衡量医院服务质量的重要指标。本文就集束化护理在疼痛管理中应用现状进行总结分析, 包括在外科疼痛、肿瘤疼痛等中应用, 以期为集束化护理在疼痛管理中的深入研究提供参考与借鉴。)